2018
DOI: 10.1084/jem.20172048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UGT8 suppresses basal-like breast cancer progression by attenuating sulfatide–αVβ5 axis

Abstract: Cao et al. show that UGT8 promotes BLBC progression through activating sulfatide–αVβ5 axis. ZA is identified as a direct inhibitor of UGT8 and suppresses BLBC progression, suggesting that inhibition of UGT8 offers a promising opportunity for treating BLBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…Because only adenocarcinoma tumors exhibited both high FA2H and UGT8, this suggests that combined FA2H and UGT8 expression could drive increased 2-hydroxyHexCer levels in adenocarcinomas. Our results strongly argue that a combination of FA2H and UGT8 expression drives the synthesis of 2-hydroxyHexCer, the exact mechanism accounting for the accumulation of these metabolites specifically in adenocarcinomas, which should be confirmed by ulterior investigations of sulfatides and gangliosides, which were also linked with cancer metastasis (35,36) and multi-drug resistance (37). Aligning with the theory that complex metabolic alterations, rather than single molecule levels, should be taken into account for delineating mechanisms of disease, low FA2H was associated with tumor growth and patient survival in gastric tumors (38), but UGT8 is not overexpressed in gastric tumors in Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Because only adenocarcinoma tumors exhibited both high FA2H and UGT8, this suggests that combined FA2H and UGT8 expression could drive increased 2-hydroxyHexCer levels in adenocarcinomas. Our results strongly argue that a combination of FA2H and UGT8 expression drives the synthesis of 2-hydroxyHexCer, the exact mechanism accounting for the accumulation of these metabolites specifically in adenocarcinomas, which should be confirmed by ulterior investigations of sulfatides and gangliosides, which were also linked with cancer metastasis (35,36) and multi-drug resistance (37). Aligning with the theory that complex metabolic alterations, rather than single molecule levels, should be taken into account for delineating mechanisms of disease, low FA2H was associated with tumor growth and patient survival in gastric tumors (38), but UGT8 is not overexpressed in gastric tumors in Fig.…”
Section: Discussionsupporting
confidence: 61%
“…34). In particular, sulfatide blockage decreases breast cancer cell migration and metastasis through different mechanisms, highlighting leptin binding (38) or integrin alpha V regulation (39). Based on motility assays data after sulfatide blockage, our working hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…First, bisphosphonates inhibit the growth of neoplastic cells in vitro. (17,18) Third, observational studies have reported that oral bisphosphonate use is associated with fewer first breast cancers (19)(20)(21) ; reduced risk of contralateral breast cancer (OR = 0.4) (22) ; reduced risk of a combined endpoint of recurrence, second primary breast cancer, and breast cancer mortality (23) ; and reduced risk of skeletal metastases in early breast cancer. (16) Second, preclinical studies show antitumor effects of bisphosphonates in animals, reducing tumor burden in bone and in non-osseous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Second, preclinical studies show antitumor effects of bisphosphonates in animals, reducing tumor burden in bone and in non-osseous tissues. (17,18) Third, observational studies have reported that oral bisphosphonate use is associated with fewer first breast cancers (19)(20)(21) ; reduced risk of contralateral breast cancer (OR = 0.4) (22) ; reduced risk of a combined endpoint of recurrence, second primary breast cancer, and breast cancer mortality (23) ; and reduced risk of skeletal metastases in early breast cancer. (24) The UK General Practice Database showed reduced risk of all cancers, and of breast and colorectal cancers specifically, in bisphosphonate users, (25) and a nationwide Danish database suggested protection against colon cancer with alendronate use.…”
Section: Discussionmentioning
confidence: 99%